2011
DOI: 10.1007/s10614-011-9262-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring US Business Cycles with Bivariate Loops Using Penalized Spline Regression

Abstract: The phrase business cycle is usually used for short term fluctuations in macroeconomic time series. In this paper we focus on the estimation of business cycles in a bivariate manner by fitting two series simultaneously. The underlying model is thereby nonparametric in that no functional form is prespecified but smoothness of the functions are assumed. The functions are then estimated using penalized spline estimation. The bivariate approach will allow to compare business cycles, check and compare phase lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…An economy with rapid shifts between regulation and de-regulation. In [63], Kauermann, Teuber and Flaschel found that the corresponding time series of the US economy for the period 1955-2005 yield a different Fig. 17: The long-phase wave in (c) seems to dipsy-doodle and lacks any remembrance of a cycle, presumably due to the state interventions of price and wage-stops of the Nixon administration and the abolition of union influence by the Reagan administration.…”
Section: Multiple Time Scales Of Economy -Short and Long Wavesmentioning
confidence: 99%
See 3 more Smart Citations
“…An economy with rapid shifts between regulation and de-regulation. In [63], Kauermann, Teuber and Flaschel found that the corresponding time series of the US economy for the period 1955-2005 yield a different Fig. 17: The long-phase wave in (c) seems to dipsy-doodle and lacks any remembrance of a cycle, presumably due to the state interventions of price and wage-stops of the Nixon administration and the abolition of union influence by the Reagan administration.…”
Section: Multiple Time Scales Of Economy -Short and Long Wavesmentioning
confidence: 99%
“…3) shows the evolution of the employment rate of workers in the sphere of production e(t) and its consequences for the income distribution between capital and labor v(t) over longer periods. To explore the emergence of two characteristic time scales in these two variables, we refer to [63]: they assume that y(t) := (e(t), v(t)) follows a long term trend c(t) = (c 1 (t), c 2 (t)) and a business cycle fluctuation g(t) = (g 1 (t), g 2 (t)), and model y(t) = c(t) + g(t) + ε(t) with an error term ε(t). In that way, the data can point to two essential aspects of economic crises in capitalism that otherwise are nowadays disguised behind GDP data, namely…”
Section: Multiple Time Scales Of Economy -Short and Long Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, scholars such as Goldstein (1999), Barbosa-Filho and Taylor (2006), Moura Jr. and Ribeiro (2013), Basu et al (2013), Kiefer and Rada (2015), Barbosa-Filho (2016), and more recently Grasselli and Maheshwari (2018) provided parametric quantitative evidence. Non-parametric treatments have also received some attention by Kauermann et al (2012). Furthermore, Barrales and von Arnim (2017), using quarterly data for the United States, have decomposed employment, utilisation, and income distribution time series into wavelets of varying periodicity and showed the existence of cycles a la Goodwin.…”
Section: Introductionmentioning
confidence: 99%